Australian general practice nurse's knowledge, attitudes and practices regarding influenza vaccination: a cross‐sectional survey. Issue 17 (1st July 2016) - Smith, Sarah; Sim, Jenny; Halcomb, Elizabeth
Abstract : Aims and objectives: The aim of this study was to examine the knowledge, attitudes and practices of Australian general practice nurses (GPNs) regarding influenza vaccination. Background: Despite the evidence for the benefits of influenza vaccination, vaccination rates remain sub‐optimal. The knowledge, attitudes and practices of nurses both affects vaccination rates and the advice given to consumers. Given their significant role in opportunistic and planned vaccinations, GPNs are in an optimal position to positively influence vaccination rates. Design: A descriptive cross‐sectional survey was used. Methods: GPNs were recruited by email to complete an online survey. The survey tool comprised the King's College Nurses' Influenza Vaccination Questionnaire and adapted demographic items. Data analysis used descriptive and inferential statistics. Open‐ended questions were analysed using thematic analysis. Results: Most of the 85 respondents had received the seasonal influenza vaccination in the last year ( n = 67; 78·8%); fewer received the H1N1 vaccination ( n = 54; 63·5%). Intention to receive vaccination was affected by previous vaccination. Those who had received the seasonal influenza vaccine in the last year had a higher total knowledge score. The seasonal and total influenza knowledge score was high, with lower scores on the H1N1 sub‐scale. A positive correlation was identified between influenza knowledge and risk perception. Conclusions: This study highlighted the high level of knowledge amongst GPNs related to seasonal influenza, whilst identifying a knowledge deficit around the H1N1 items. It demonstrated that GPN's knowledge of seasonal influenza was related to vaccination status and risk perception. Further research is required to explore how this translates into the advice GPNs give to consumers. Relevance to clinical practice: Influenza vaccination should be considered as a key topic for GPNs ongoing professional development. The evidence for links between education and vaccination uptake should encourage employers to facilitate opportunities for this training. Future efforts to increase vaccination uptake in nurses should promote the benefits of vaccination in protecting the individual rather than as a professional responsibility.